GAMIFICATION IN LANGUAGE ASSESSMENT: ENHANCING MOTIVATION AND PERFORMANCE - Abdushukurova Oysha Sirojiddin qizi; Khonsaidova Maktuba Makhamadalievna (TADQIQOTLAR, 2026)
ABSTRACT   This  study  explores  the  role  of  gamification  in  enhancing  motivation  and improving performance in language assessment settings. It examines how game-based elements influence learners’ attitudes, participation levels, and achievement outcomes. Drawing  on  contemporary  educational  theories  and  empirical  research,  the  paper highlights the psychological mechanisms underlying gamified learning environments, including increased engagement, immediate feedback, and goal-oriented progression.